Windows Server 2008 server core administrator's pocket consultant - Tulloch, Mitch (Microsoft Press, 2009)
"Portable and precise, this pocket-sized guide delivers ready answers for administering your Server Core installation. Zero in on essential support and maintenance tasks using quick-reference tables, instructions, and lists. You'll get the focused information you need to solve problems and get the job done - whether at your desk or in the field!"--Jacket.